Laje de Santos: a dive site recreated in virtual reality - Gnecco, Bruno Barberi; Guimaraes, Marcelo De P (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2022)
This project used 2D and 3D graphics to raise awareness and information about the Laje de Santos Marine State Park (Parque Estadual Marinho da Laje de Santos), the first marine park of the State of São Paulo in Brazil. The project’s main goal was to allow people from all over Brazil and the world to virtually visit the park, since visiting the park requires two hours of navigation on a speed boat and a SCUBA diving certification to see the underwater life. Through our project people can make simulated virtual reality SCUBA dives, learn about the fauna that inhabits the park and the marine environment. We detail in this paper the process to reconstruct the park in 3D and create the VR experience. This project is available on a website with text, images, videos and 3D content that works on any browser with no need of a separate app download, and has its full source code published.